Analysis of the Effect of Hypertension Gymnastics on Lowering Blood Pressure in Hypertension Patients in the Tapunggaya Health Center Work Area - Suriani, Lili; Sunarsih, Sunarsih; Rahmawati, Rahmawati (Magister Kesehatan Universitas Mandala Waluya, 2024)
Introduction: WHO states that hypertension has attacked 22% of the world's population. While the number of hypertension in Southeast Sulawesi itself reached 26.53% or 314,454. One of the non-pharmacological treatments for hypertension is hypertension exercise and the DASH Diet (Dietary Approaches to Stop Hypertension) is a diet pattern aimed at lowering blood pressure by limiting salt intake, saturated fat, and increasing food intake that contains a lot of potassium, calcium, magnesium and high-fiber foods. This study is to analyze the Effect of Hypertension Exercise on Lowering Blood Pressure in Hypertension Patients in the Tapunggaya Health Center Work Area. Method: This type of research is quantitative with an experimental approach with a pretest-posttest design. The research sample was 284 people using a simple random sampling technique. The data collection tool used a blood measurement observation sheet. The statistical test used was the Paired Sample T-Test. Result: Obtained Results before hypertension exercise treatment on decreasing systolic blood pressure average 148 after treatment average blood pressure 134 mmHg. And the results before treatment diastolic blood pressure average 91 and 96 mmHg after treatment average mmHg. Based on the T-test obtained (P value = 0.00 with alpha <0.05). It can be concluded that there is a significant effect between hypertension exercise on decreasing blood pressure. Conclusion: There is an effect of hypertension exercise therapy to lower blood pressure in hypertension sufferers. It is expected that hypertension sufferers can continue hypertension exercise to lower blood pressure.